How Effective is Physical Therapy for Common Low Back Pain Diagnoses?: A Multivariate Analysis of 4597 Patients. Issue 16 (15th August 2016) - Eleswarapu, Ananth S.; Divi, Srikanth N.; Dirschl, Douglas R.; Mok, James M.; Stout, Christopher; Lee, Michael J.
Abstract : Study Design: A retrospective review. Objective: The aim of this study is to evaluate whether the treatment of low back pain with physical therapy results in clinically significant improvements in patient-reported pain and functional outcomes. Summary of Background Data: Low back pain is a major cause of morbidity and disability in health care. Previous studies have found poor efficacy for surgery in the absence of specific indications. A variety of nonoperative treatments are available; however, there is scant evidence to guide the practitioner as to the efficacy of these treatments. Methods: Four thousand five hundred ninety-seven patients who underwent physical therapy for the nonoperative treatment of low back pain were included. The primary outcome measures were pre-and post-treatment scores on the Oswestry Disability Index (ODI), Numeric Pain Rating Scale (NPRS) during activity, and NPRS during rest. Previously published thresholds for minimal clinically important difference (MCID) were used to determine the proportion of patients meeting MCID for each of our outcomes. Patients with starting values below the MCID for each variable were excluded from analysis. Logistic regression analysis was used to determine patient risk factors predictive of treatment failure. Results: About 28.5% of patients met the MCID for improvement in ODI. Presence of night symptoms, obesity, and smoking were predictors of treatment failure for ODI. Fifty-nine percent of patients met the MCID for improvement in resting NPRS, with a history of venous thromboembolism, night symptoms, psychiatric disease, workers' compensation status, smoking, and obesity predictive of treatment failure. Sixty percent of patients met the MCID for improvement in activity NPRS, with night symptoms, workers' compensation status, and smoking predictive of treatment failure. Conclusion: We observed that a substantial percentage of the population did not meet MCID for pain and function following treatment of low back pain with physical therapy. Common risk factors for treatment failure included smoking and presence of night symptoms. Level of Evidence: 4